Gender, Sex, and the Role of Stereotypes in Evaluations of Hillary Clinton and the 2016 Presidential Candidates. (2nd April 2020) - Conroy, Meredith; Joesten Martin, Danielle; Nalder, Kim L.
ABSTRACT: The prevalence of gender stereotypes in US politics is well documented, yet questions remain: do voters think of presidential candidates in gendered terms and, if so, is there a connection to support? To answer these questions, we analyze survey respondent descriptions of 2016 primary and general election presidential candidates. We assess whether descriptions are gendered, if gender slurs are applied more to the female candidate, and whether these descriptions are associated with candidate support. We find that Hillary Clinton is described in more masculine than feminine terms, with a higher frequency of gendered slurs than other candidates. Bernie Sanders is described with more feminine than masculine traits, and Donald Trump is overwhelmingly described as masculine. As expected, Trump's support is associated with more masculine and less feminine trait attributions. However, masculine descriptions of Clinton are associated with lower levels of support, consistent with role congruity theory and the persistence of the double bind for female candidates.